2011
DOI: 10.1039/c0cc04198j
|View full text |Cite
|
Sign up to set email alerts
|

In situassembly of gold nanoparticles on nitrogen-doped carbon nanotubes for sensitive immunosensing of microcystin-LR

Abstract: A simple and green method was developed for in situ assembly of gold nanoparticles on nitrogen-doped carbon nanotubes, and the resulting Au/nitrogen-doped carbon nanotubes nanocomposite was used as an immobilization scaffold of antibody for sensitive immunosensing of microcystin-LR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 25 publications
0
49
0
2
Order By: Relevance
“…A simple strategy for using the Au/N-CNT nanocomposites as platform for the immobilization scaffold of the antibody for sensitive immunosensing of microcystin-LR is presented. This strategy allows the successful immobilization and enhances the catalytic efficiency of the antibodies by conjugations of the doped nanotubes and GNPs compared with the naked N-CNTs in this experiment [17]. Recently, Deng et al have explored a novel double functionalization of a CNT delivery system containing polyelectrolyte and CdS quantum dots as the fluorescent labeling probes via electrostatic assembling [122].…”
Section: Sensors/biocatalystmentioning
confidence: 99%
See 2 more Smart Citations
“…A simple strategy for using the Au/N-CNT nanocomposites as platform for the immobilization scaffold of the antibody for sensitive immunosensing of microcystin-LR is presented. This strategy allows the successful immobilization and enhances the catalytic efficiency of the antibodies by conjugations of the doped nanotubes and GNPs compared with the naked N-CNTs in this experiment [17]. Recently, Deng et al have explored a novel double functionalization of a CNT delivery system containing polyelectrolyte and CdS quantum dots as the fluorescent labeling probes via electrostatic assembling [122].…”
Section: Sensors/biocatalystmentioning
confidence: 99%
“…The doped CNTs can be used as platforms for the multiple derivatization by loading their surface with other therapeutic agents (treatment), fluorescent, magnetic, or radionuclide probes (tracking), active recognition moieties (targeting), and with nanoparticles. Substantial work has also been carried out in alkaline/acidic/neutral media anchoring metals and their oxides such as Pt [127], Pd [128,129], Au [17,64], Cu [130], Fe [131], Ga [132], ZnO [133], and SnO 2 [70] over the N-CNT surfaces. The past studies showed a much higher electrocatalytic oxidation for the alcohols over Pt/N-CNT compared to the activity shown by Pt/C [5].…”
Section: Electrocatalytic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results (Table 2) of the experiments to find the relationship between the chemiluminescence intensity and the concentration of HRP labeled microcystin (Zhang et al 2011) and 30 min for fluorescent strip assay (Khreich et al 2010) No need of microcystin LR standards Both of gold nanoparticle assay (Zhang et al 2011) and fluorescent strip assay (Khreich et al 2010) ) of 0.979. Therefore, the strip chemiluminescence assay system developed in this work can be used effectively for the trace analysis of microcystin in a water sample.…”
Section: Preparation Of Water Samplementioning
confidence: 99%
“…The use of monoclonal antibodies that selectively recognized microcystin could enhance the detection limit up to 10 fmol mL -1 (Khreich et al 2009). Recently, the colorimetric immunochromatographic assay method (Zhang et al 2011) using gold nanoparticles and the fluorescent strip assay method (Khreich et al 2010) using a monoclonal antibody of microcystin were developed.…”
Section: Preparation Of Microcystinsmentioning
confidence: 99%